2021
DOI: 10.15388/actpaed.2021.46.6
|View full text |Cite
|
Sign up to set email alerts
|

The University Administrative Staff Perception of Inclusion in Higher Education

Abstract: This study investigates university administrative staff perception of inclusion in higher education at the university level. The study uses the University of Latvia as a case to answer the following research questions: What constitutes inclusion in university education, how accessibility is provided? What are the support systems provided for diverse students? What support and training are provided to administrative and academic staff to ensure that the educational needs of diverse student bodies are met? The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Among them, the lack of preparation of teachers to use a methodology that promotes inclusion in the classroom according to the needs of their students stands out [39]. These results coincide with other studies that have been carried out on the lack of teacher training to cater for these students in higher education [52,53]. They also mention the difficulties of access to material resources, since in most cases they are not adapted to their needs or are limited [34,40,46,54].…”
Section: Discussionsupporting
confidence: 75%
“…Among them, the lack of preparation of teachers to use a methodology that promotes inclusion in the classroom according to the needs of their students stands out [39]. These results coincide with other studies that have been carried out on the lack of teacher training to cater for these students in higher education [52,53]. They also mention the difficulties of access to material resources, since in most cases they are not adapted to their needs or are limited [34,40,46,54].…”
Section: Discussionsupporting
confidence: 75%
“…Stentiford and Koutsouris (2021) noted that inconsistency and fragmentation in the perception of inclusive education significantly hinder the dissemination of inclusion in higher education institutions. The study focusing on the perception of inclusion in higher education by university administrative staff emphasizes that in Latvia, faculty members do not undergo training on how to work with student diversity (Nimante et al, 2021). In general, the preparation of teachers for implementing inclusive education is a widespread problem worldwide (Bunbury, 2020; Collins et al, 2018; Martins et al, 2018; Sanahuja et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focus on the lack of faculty members preparation to use methodology that promotes inclusion according to students' needs (Heiman et al, 2017; Nimante et al, 2021; Zubilllaga del Río et al, 2013). It is also reported that there is a general problem of providing services to meet the requests and needs of students with disabilities at the university level (Björnsdóttir, 2017; Yusof et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The need for inclusivity in HE has already been highlighted by Jaegler (2022), who states that inclusivity must be understood as a concept for all stakeholders of a higher education institution (HEI): students, employees, alumni, and partners. However, the principles of inclusivity in HE are not so self-evident, which has been pointed out by several researchers (Nīmante et al, 2021;Stentiford & Koutsouris, 2021). One of the reasons researchers point to is that those working in HE do not have an understanding of how to provide inclusive education (Nīmante et al, 2021;Bunbury, 2020) or how to assess student achievement in light of inclusive education principles (Griskevica et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the principles of inclusivity in HE are not so self-evident, which has been pointed out by several researchers (Nīmante et al, 2021;Stentiford & Koutsouris, 2021). One of the reasons researchers point to is that those working in HE do not have an understanding of how to provide inclusive education (Nīmante et al, 2021;Bunbury, 2020) or how to assess student achievement in light of inclusive education principles (Griskevica et al, 2022).…”
Section: Introductionmentioning
confidence: 99%